Gender Awareness Factor in Coastal Women Entrepreneur’s Efforts to Support Family Economic Resilience - Intan Fitranisa; Elizabeth Adelyne Putri; Fikri Raihan; Zahra Najla Octavian; Hannanah Amaliya; Nayya Latifah Rahmadini (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2026)
Coastal communities in Indonesia continue to face structural challenges such as poverty, limited access to education, and patriarchal social systems, which place women in vulnerable social and economic positions. Despite these constraints, coastal women have increasingly participated in entrepreneurial activities to support household income and community economic resilience. This study aims to analyze gender awareness among coastal female entrepreneurs and examine the challenges and empowerment strategies that shape their entrepreneurial experiences in Tambak Wedi Village, Surabaya. This study employed a qualitative descriptive approach using unstructured observation and in-depth interviews with ten coastal female entrepreneurs selected based on business activity, duration of business operation, and active involvement un family economic support. Data were analyzed through data reduction, categorization, interpretation, and thematic analysis. The findings show that gender awareness among coastal female entrepreneurs reflected in their active economic participation, shared domestic responsibilities, and involvement in household decision-making. However, women continue to face structural barriers, including gender stereotypes, double burdens, limited access to government support, institutional collaboration, and digital technology play important roles in strengthening women’s entrepreneurial capacity and economic independence. This study concludes that achieving gender equality in coastal communities requires inclusive empowerment strategies that expand women’s access to training, financial support, and technology while transforming patriarchal social perceptions of women’s roles in both domestic and public spheres.